Approaching psychoanalysis : an introductory course - Smith, David Livingstone, 1953- (Karnac Books, 1999)
A comprehensive user-friendly introductory account of Freudian theory and other major currents in psychoanalytic thought. It also includes biographical material on the major theorists. It helps to clear up many misconceptions about psychoanalytic theory and will be useful for students and professionals alike. 248 pages.